OWNERSHIP IN THE QUR’AN (A Thematic Study of Qur’anic Verses) - Faridatus Shofiyah (Sekolah Tinggi Agama Islam Almuhammad Cepu, 2021)
Qur’an as the source of guidance assists human beings to develop their human resources in order to get welfare. One of way to get the welfare is with property. The spirit of Islamic teaching is making the rich and develops society. Ironically, there are still many problems related to backwardness in economy, poverty, jobless, and enormous employee. This phenomenon is caused by two factors, namely internal and external. Internal factor comes from man self who does not actualize his potential as hard as possible to change the condition. Meanwhile, external factors come beyond self, for example the coming of economic globalization, corruption, collusion, and nepotism that caused inequity distribution of wealth/ property. Therefore, this paper focuses on ownership that is supported by the verses of Qur’an. To make this research systematic, the researcher uses the method of thematic tafsir. As a thematic study, first, it elaborates ownership as the main theme through its definition, theory and any other discussions in relation to it. Second, it tries to explore some terms such as malaka, istakhlafa, and waratsa and also explore some terms that have tight correlation with ownership, and some verses of Qur’an supporting ownership. Dealing with the contribution of this research to Qur’anic studies, it analyzes the point of view in Qur’an on ownership.